The Impact of Cybersecurity Breaches on Firm’s Market Value: the Case of the USA - G. K. Issayeva; E. E. Zhussipova; A. N. Aitymbetova; A. S. Kuralbayeva; D. B. Abdykulova (Экономика: стратегия и практика, 2024)
In the context of global digitalization trends, the problem of the impact of cyberattacks on the company is significantly relevant. This article is devoted to the impact of cyberattacks on the firms’ market value since it is an indicator of firm performance. The authors used the event study methodology to study the impact of cyberattacks on the firm’s market value. In addition, linear regression analysis (OLS) was applied to study the factors influencing cumulative abnormal returns (CAR). The paper’s central hypothesis is the assumption that a cyberattack announcement is supposed to change market reaction, which is predicted to be harmful since cybercrime incidents can lead to high implicit and explicit costs. Therefore, an adverse market reaction reflects negative CAR during the event. The paper explores the effect of firm-specific and attack-specific characteristics of cyberattacks on the CAR with the data of cyberattacks for US firms from 2011 to 2020. Thus, the impact of cyberattacks on CAR by industry type and firm size was examined. Also, the type of cybercrime that is more harmful to the company was identified. The study results confirm the central hypothesis and show that cyberattacks negatively affect the firms’ market value. In addition, it was found that the market reaction to the breach is more harmful to small firms. Thus, large firms have advantages over medium and small ones in sustaining financially during cyberattacks. Additionally, the paper defines no consistent evidence that market reaction to cyberattacks depends on firm and breach types.